The Chlorine Reduction in Edamame by Water-Ozonated Minimally Process - Silvia Oktavia Nur Yudiastuti; Rizza Wijaya (Publikasi Indonesia, 2021)
The objective of this article was to study the effect of washing edamame using ozonated water to reduce residual chlorine contained in edamame through a continuous washing process. Chlorine residue in edamame was caused by the use of fertilizers and pesticides that contain chlorine compounds. The research method used was descriptive explanatory research consist of two treatment levels of ozonation time (0, 10, and 15 minutes) and ozone contact time (0, 12, 18, and 24 minutes) which were repeated twice. The residual chlorine and pesticide concentrations were calculated using the titration method. Based on research results, ozone can reduce chlorine in edamame. The lowest detected chlorine was in edamame which had been washed using ozone water with an ozonation time of 15 minutes with the amount of chlorine reduced by 56%. The longer the contact time, the greater the amount of reduced chlorine and the lower the concentration of ozone remaining in the washing water. Based on the research results, a brief conclusion that can be explained was ozone could reduce chlorine in edamame caused by fertilizer and disinfectant overuse until 50%.